The Dissemination of the Qur’an in Urban Societies: PPPA Daarul Qur’an and its Social Activities in Yogyakarta - Iin Nur Zulaili (Ulumuna, 2018)
This paper explores one of the leading Islamic educational institutions and its roles in the dissemination of the Qur’an and community development in an urban setting in Indonesia. The rising trend of the program of the memorization of the Qur’an (taḥfīẓ) has attracted young Muslim generations. This empirical study finds that the PPPA Daarul Qur’an develops an Islamic institution that focuses mainly on the production of the Qur’an memorizers and the dissemination of this program throughout the country. With the large support from broader Muslim community and international networking, the institution is now a home for thousand students coming from across the country. In addition to regular study of the Qur’an, the institution also run charity programs that target the poor to offer easy access to Islamic education. By incorporating education and social service, the PPPA plays important roles not only in enhancing Islamic education but also in developing Muslim community.